Bamboo in the brain: Impalement injury over orbito-cranial region via superior orbital fissure - Pokhrel, Bibesh; Thapa, Amit (Nepal Journal of Neuroscience, 2021)
Intracranial wooden foreign bodies due to transorbital penetrating injury sparing orbital globe are relatively rare with no reported cases till date. A multidisciplinary approach with multiple imaging modalities is needed for preoperative surgical planning. In this case report, we report a case of 3-year-old male who presented to our emergency department with history of fall from 5 feet with no vision over right eye. 2cm cut injury with sutures in situ was present over nasal ridge with pus discharge. CT scan head showed foreign body over temporal region. Right fronto-temporo-orbito-zygomatic craniotomy with removal of foreign body was done. Deep seated abscess seen over temporal fossa was evacuated and post-operatively intravenous antibiotics was continued. Contrast enhanced CT repeated on 15th post-operative day showed no remaining abscess or foreign body. The patient was discharged on oral antibiotics. The wound healed completely with no improvement of vision in 1-week follow-up. Keywords: brain abscess, orbito-cranial penetrating injury, wooden foreign body